Multinationals and development - Rugman, Alan M.; Doh, Jonathan P. (New Haven : Yale University Press, 2008)
"In this book, Rugman and Doh question some of the traditional development assumptions and paradigms, arguing that many are outdated or misguided. Drawing from recent research in international business and multinational management, they bring an incisive, microeconomic, "on the ground" perspective to the mechanisms by which MNEs affect growth and development. They specifically evaluate the impact of MNEs on the processes and outcomes of development, as well as the influence of civil society, NGOs, and government policies on multinationals, especially in Asia. Examining the relationship between MNEs and the poorer countries in the world, the authors show that emerging economies have benefited greatly from MNEs, increasing these countries' per capita incomes and improving the overall internal distribution of these incomes."--Jacket.
Introduction to the key issues -- Foreign direct investment and development -- Multinational enterprise strategies and development -- The role of international institutions -- The contributions and impact of civil society -- Institutional governance and development -- Multinational enterprises from emerging economies -- Multinationals and development in Asia -- Yang multinationals -- Conclusions.
Includes bibliographical references (pages 209-229) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: International business enterprises; International trade; Economic development; Entreprises multinationales; Commerce international; Développement économique.; economic development; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; BUSINESS & ECONOMICS -- International -- Economics; Economic development; International business enterprises; International trade; Direktinvestition; Multinationales Unternehmen; Internationales Unternehmen -- Entwicklungsländer.; Kapitalanlage -- Entwicklungsländer.; Wirtschaftsentwicklung -- Internationales Unternehmen; Internationales Unternehmen -- Wirtschaftsentwicklung; Multinationales Unternehmen; Wirtschaftswachstum; Entwicklungsländer.; Asien; Industry